2010
DOI: 10.1002/jgm.1495
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of inducible nitric oxide synthase gene therapy: targeting early stage and advanced prostate cancer

Abstract: Highly significant tumour growth delay coupled with no detrimental side-effects were observed following treatment with the PSMA/iNOS and hOC/iNOS constructs. We consider that these findings provide a basis for the development of systemically delivered PSMA/iNOS or hOC/iNOS targeting early stage and advanced prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Indeed, our observations were in agreement with previous studies on the internalization of RALA/plasmid DNA nanoparticles, which occurs rapidly and relies on both clathrin- and caveolin-dependent processes 1 . We have demonstrated previously that iNOS gene therapies delivered intratumorally produce an impressive therapeutic benefit9, 10, 11, 12, 19 and described reporter gene expression when the Luciferase gene was delivered systemically using RALA, 1 but this is the first description of systemic RALA-mediated therapeutic transgene delivery and the first description of systemically delivered iNOS for cancer gene therapy. Both iNOS gene therapy constructs provoked inhibition of clonogenicity in vitro.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Indeed, our observations were in agreement with previous studies on the internalization of RALA/plasmid DNA nanoparticles, which occurs rapidly and relies on both clathrin- and caveolin-dependent processes 1 . We have demonstrated previously that iNOS gene therapies delivered intratumorally produce an impressive therapeutic benefit9, 10, 11, 12, 19 and described reporter gene expression when the Luciferase gene was delivered systemically using RALA, 1 but this is the first description of systemic RALA-mediated therapeutic transgene delivery and the first description of systemically delivered iNOS for cancer gene therapy. Both iNOS gene therapy constructs provoked inhibition of clonogenicity in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously employed numerous transcriptional targeting strategies. Utilization of the prostate-specific membrane antigen (PSMA) promoter elicited iNOS transgene expression in prostate cancer lines but not in colon or breast carcinoma lines 11 . We have also used inducible promoters to control iNOS expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also shown that PEDF concomitantly reduces cell proliferation and up-regulates iNOS in highly metastatic prostate cancer cells (Filleur, personal unpublished data) implying that PEDF could regulate the expression of iNOS in various cell types. These data could be of interest as iNOS over-expression has been recently described as increasing cytotoxicity in androgen-dependent and -independent prostate cancer cell lines (53,54). iNOS gene therapy also enhances the toxicity of cisplatin in prostate cancer cells (55).…”
Section: Discussionmentioning
confidence: 90%